(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Purpose: This study examines retail investors' awareness, perceptions, and willingness to invest in green bonds within India's evolving sustainable finance landscape. It seeks to bridge the critical knowledge gap between policy-driven green finance initiatives and actual retail market participation by identifying key barriers and enablers influencing investment behaviour. The research provides empirical insights into how demographic factors, financial literacy, and market structures shape sustainable investment decisions in emerging economies. Methodology: The study employs a mixed-methods approach, combining quantitative analysis of survey responses from 100 retail investors with qualitative thematic analysis of 20 in-depth interviews. Data collection focused on four dimensions: awareness levels, risk-return perceptions, investment willingness, and structural barriers. Statistical analysis included descriptive metrics and correlation studies, while interview transcripts were coded using NVivo to identify recurring themes. The sample was stratified across age groups, education levels, and occupational categories to ensure representative insights. Findings: The results reveal moderate but uneven awareness, with higher recognition among older (46+ years) and more educated investors. Key findings include: (1) significant conceptual confusion regarding green bonds' environmental purpose, with many associating them incorrectly with infrastructure (27.6%) and education (25.0%); (2) equal weighting of financial returns (20.5%) and environmental impact (20.5%) in investment decisions; (3) pervasive trust deficits, with 43.6% expressing scepticism due to greenwashing concerns; and (4) structural barriers including limited accessibility and preference for traditional instruments. Notably, 41.6% of respondents demonstrated positive reception, suggesting untapped market potential conditional on policy interventions. Originality: This study contributes novel insights into sustainable finance behaviour in three key dimensions. First, it provides the first comprehensive assessment of India's retail green bond market, filling a critical gap in emerging market research. Second, it introduces an integrated framework analysing both cognitive barriers (trust deficits, knowledge gaps) and structural constraints (market access, liquidity). Third, the findings challenge conventional assumptions by demonstrating how Indian investors equally weigh financial and ethical considerations—a departure from dominant Western models emphasizing environmental values. The research offers evidence-based policy recommendations for accelerating retail participation in sustainable finance transitions.